A Review of the Effect of Processing Variables on the Fabrication of Electrospun Nanofibers for Drug Delivery Applications. (13th February 2013) - Pillay, Viness; Dott, Clare; Choonara, Yahya E.; Tyagi, Charu; Tomar, Lomas; Kumar, Pradeep; du Toit, Lisa C.; Ndesendo, Valence M. K.
Abstract : Electrospinning is a fast emerging technique for producing ultrafine fibers by utilizing electrostatic repulsive forces. The technique has gathered much attention due to the emergence of nanotechnology that sparked worldwide research interest in nanomaterials for their preparation and application in biomedicine and drug delivery. Electrospinning is a simple, adaptable, cost-effective, and versatile technique for producing nanofibers. For effective and efficient use of the technique, several processing parameters need to be optimized for fabricating polymeric nanofibers. The nanofiber morphology, size, porosity, surface area, and topography can be refined by varying these parameters. Such flexibility and diversity in nanofiber fabrication by electrospinning has broadened the horizons for widespread application of nanofibers in the areas of drug and gene delivery, wound dressing, and tissue engineering. Drug-loaded electrospun nanofibers have been used in implants, transdermal systems, wound dressings, and as devices for aiding the prevention of postsurgical abdominal adhesions and infection. They show great promise for use in drug delivery provided that one can confidently control the processing variables during fabrication. This paper provides a concise incursion into the application of electrospun nanofibers in drug delivery and cites pertinent processing parameters that may influence the performance of the nanofibers when applied to drug delivery.